Association Between Drinking Water Sources and Osteoarthritis Incidence in Chinese Elderly Population: National Population-Based Cohort Study - Zhang, Yangchang; Wu, Tingting; Shen, Shisi; Xiong, Yang; Wang, Xu; Yang, Jialu; Chen, Xirui; Lu, Yanjun; Lei, Xun (Frontiers in Medicine, 2022)
Background： Few studies reported the association between unsafe water with incident osteoarthritis (OA) among the elderly, as the vulnerable group susceptible to toxic environmental factors. This study aimed to examine the effect of drinking water sources on the risk of OA in the Chinese elderly population. Methods： Data were drawn from the China Longitudinal Healthy Longevity Survey (CLHLS), and a longitudinal study for 16 years was conducted. All participants aged ≥ 65 years at baseline were potentially eligible. The information on drinking water sources was recorded via a structured questionnaire. The kinds of water sources were divided into the well, the surface water, the spring water, and the tap water. The health outcome of the study was OA. Cox proportional hazards models, adjusted socio-demographics, lifestyle, and chronic disease were used to estimate the hazard ratio for OA. The subgroup analyses were assessed the potential interactive effect. Results： This study included 12,543 participants. The mean survival time of follow-up was 14.56 years after being restricted to the longest follow-up time. In the cohort, 1,585 suffered from OA. Compared to tap water, drinking from well water and spring water was associated with a lower risk of mortality in the full model, respectively (HR: 1.37, 95%CI: 1.22-1.54; HR: 1.34, 95%CI: 1.03-1.74). The effects of modifications from socioeconomic status, lifestyles, and health conditions were non-significant except for age (P for interaction < 0.05). Sensitivity analysis indicated that the association between drinking-water sources and incident OA was robust after conducting multiple imputations for missing data, excluding deaths in the first year of follow-up and participants with a history of the disease, respectively. Conclusion： Drinking tap water was associated with a lower risk of OA among older adults in China. The process of clean water sources as a marker of decreased OA and arthritis diseases risks may need to be revisited in low- and middle-income countries (LMICs).